Integration of High Reliability Distribution System in Microgrid Operation - Khodayar, M. E.; Barati, M.; Shahidehpour, M. (IEEE transactions on smart grid, 2012)
In this paper, the application of high reliability distribution system (HRDS) in the economic operation of a microgrid is studied. HRDS, which offers higher operation reliability and fewer outages in microgrids, is applied to looped networks in distribution systems. The microgrid model in this study is composed of distributed energy resources (DER) including distributed generation (DG), controllable loads, and storage. The microgrid would utilize the local DER as well as the main grid for supplying its hourly load economically which is subject to power quality and reliability requirements. The HRDS implemented at Illinois Institute of Technology (IIT) is used as a case study along with the local DER to increase the load point reliability and decrease the operation cost of the IIT microgrid. The availability of distribution lines, main grid supply, and microgrid generation is considered using the Markov chain Monte Carlo simulation in the microgrid scenarios. The reliability indices based on frequency and duration of outages are measured at the microgrid level and the load point level, and the potential system enhancements are discussed for improving the economic operation of the IIT microgrid.